Формування професійної компетентності майбутніх фахівців з документознавства та інформаційної діяльності - Настенко, Лариса; Свердлик, Зоряна (Видавництво Львівської політехніки, 2017)
The necessity of competence approach realization in professional training of experts in records management and information activity has been specified. Recommendations concerning practical classes’ conduction in discipline-specific subjects, the usage of problematic and research methods for professional competence formation have been provided.
Keywords: компетентнісний підхід; компетенція; професійна компетентність документознавця; засвоєння матеріалу; практична реалізація